Effects of Breastfeeding Skill Training Program on Efficiency, Self-efficacy, and Exclusive Breastfeeding Rate among First-time Adolescent Mothers - Pan-inpang, Anchana; Phahuwatanakorn, Wanna; Limruangrong, Piyanun (Nursing Science Journal of Thailand, 2021)
Purpose: To examine the effects of the breastfeeding skill training program on breastfeeding efficiency at discharge and 1-month exclusive breastfeeding rate among first-time adolescent mothers. Design: Quasi-experimental study with pre-test post-test control group design. Methods: Through convenience sampling, the sample consisted of 50 mothers with normal delivery aged 15-19 years at the postpartum ward of Chiangrai Prachanukroh Hospital. They were divided into control and experimental groups with 25 each. The control group received only routine nursing care, while the other received both routine nursing care and the breastfeeding skill training program including observation, practice and self-assessment. Data were collected using a demographic characteristic questionnaire, breastfeeding self-efficacy scale short form, efficient breastfeeding and sucking assessment form, and exclusive breastfeeding record form. Data were analyzed using descriptive statistics, Independent t-test, Mann-Whitney U test, Chi-square test, Fisher exact test and Z test. Main findings: The study revealed that mothers in the experimental group had significantly higher efficient breastfeeding score at discharge and breastfeeding self-efficacy score at 1 month than that in the control group (Z = 5.36, p < .001 and Z = 5.13, p < .001, respectively). Rate of 1-month exclusive breastfeeding was also significantly higher than that in the control group (p < .05). Conclusion and recommendations: Breastfeeding skill training program can increase efficient breastfeeding at discharge and maternal self-efficacy in breastfeeding at 1 month after giving birth, and the rate of exclusive breastfeeding at 1 month. Therefore, nurses and midwives should apply the breastfeeding skill training program to promote postpartum adolescent mothers for continuing efficient exclusive breastfeeding.